Technical exercises for the execution of straight punches in boxers of the child category - Giraldo Machuat Santana; Yusimil Ramos Quian; Lázaro Ramos García (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
The present research aims to put into the hands of the coaches a material whose value in the methodological didactic can serve as a tool in the search for alternative solutions to the problems that today affect the technical and tactical preparation of our boxers from the point of view an offensive view, specifically on the effectiveness of straight blows to the face and trunk. For the accomplishment of this work a sample of 12 athletes was chosen, all belonging to the category 11-12 years of the municipality San Juan y Martínez to which as an experimental form ,the introduction of a methodology supported in a set of exercises was applied, as part of the teaching-learning process of athletes, regarding the execution of straight blows to the face and trunk, as an essential tactical offensive technical aspect in this age category to achieve victory in combat. A total of 16 observations were made to trainings and competitions to appreciate how the technique behaved in the execution of these blows by the athletes research subject. As a result there is a proposal of exercises that through a correct execution and implementation can contribute to the improvement of the effectiveness in the execution of the straight blows to the face and trunk of the boxers of the category 11 and 12 years of the combined sport nº 1 of the municipality San Juan y Martínez.